1997
DOI: 10.1055/s-2007-996102
|View full text |Cite
|
Sign up to set email alerts
|

Essential Thrombocythemia in Childhood

Abstract: In addition to the criteria of the Polycythemia Vera Study Group, positive markers for essential thrombocythemia (ET) include spontaneous BFU-E, splenomegaly, and megakaryocyte morphology in bone marrow smears and biopsy material. The hematologic features of 11 reported cases of ET in childhood showed platelet counts in excess of 1000 x 10(9)/L in all, slight leukocytosis in 8, and splenomegaly in 9. The presenting thrombohemorrhagic manifestations in 8 symptomatic cases were microcirculatory disturbances and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
(66 reference statements)
0
10
0
1
Order By: Relevance
“…As previously discussed, ET in children is not always a benign entity; the crucial question is how to identify patients who are at high risk of complications and need treatment. Most laboratory tests are of little help in predicting the clinical course of ET (Barbui et al , 1983; Michiels & Van Genderen, 1997). Occasional studies in adults (Fenaux et al , 1990), however, have shown a correlation between increased risk of haemorrhage if the platelet count is > 2000 × 10 9 /l.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…As previously discussed, ET in children is not always a benign entity; the crucial question is how to identify patients who are at high risk of complications and need treatment. Most laboratory tests are of little help in predicting the clinical course of ET (Barbui et al , 1983; Michiels & Van Genderen, 1997). Occasional studies in adults (Fenaux et al , 1990), however, have shown a correlation between increased risk of haemorrhage if the platelet count is > 2000 × 10 9 /l.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…However, with the advent of automated platelet counting, increased platelet counts and, in particular, ET are diagnosed with increasing frequency in young adults and even in childhood, although less commonly than in adults. The 11 cases of ET in children reported in the literature ( Michiels & Van Genderen, 1997) showed persistently elevated platelet counts over 1000 × 10 9 /l with thrombotic and haemorrhagic episodes occurring in eight out of 11 patients.…”
mentioning
confidence: 98%
“…Cases and reviews of cases reported in the literature indicate that the natural history, certainly in ET and PV, may be similar to that seen in adults [6, 9, 10]. The UK Childhood Myeloproliferative Diseases Registry will try to ascertain the incidence and natural history of these disorders in childhood.…”
Section: Chronic Myeloproliferative Diseasesmentioning
confidence: 99%